Sistem Kunci Elektronik Pintu Kos Menggunakan IoT Berbasis E-KTP - Ramadini, Deby (Lembaga Yasin AlSys, 2025)
The increasing demand for boarding houses in urban areas presents challenges for owners, including ensuring security, managing access, and enforcing tenant compliance with rental agreements. This research introduces an IoT-based electronic door lock system utilizing e-KTP for boarding houses to address these challenges. The system facilitates efficient and secure room access management through integration with a web server for real-time monitoring and notifications. It employs an RFID reader to authenticate e-KTP cards, with the data processed by a NodeMCU microcontroller to control a solenoid lock. For emergency situations, a pushbutton is installed to allow access from inside the room. The system records all access events and sends notifications to users, including reminders for payment deadlines and rental expiration. All data is stored in a MySQL database and accessed through a user-friendly web interface designed for tenants and landlords. Testing demonstrates the system's reliability in granting authorized access and blocking unauthorized attempts. The push button ensures secure internal use. The integration of IoT technology enhances security, convenience, and administrative efficiency in managing rental housing.